Client Satisfaction: Key Factors to Sustainability of Microfinance Institutions (MFIs) - Lamichhane, Basu Dev (Interdisciplinary Journal of Management and Social Sciences, 2021)
This paper describes the analytical picture of client protection strategy. This is descriptive research design. Client’s is an important part for instutional governace which interact different parties i.e. policy makers, political leaders, social leader/activist and gurdians of microfinance members. Responsible financing helps to Neplease microfinance institutions (MFIs) to retain clients in microfinance institutions. MFIs needs clear vision and policy regarding client’s retention. MFIs need to create the healthy and favaurable environment of microfinance sector. Responsible financial inclusion focus on transprant in the pricing, terms and condition of all financial products. It works with clients so they do not borrow more money than they can repay or use products that they do not need. The conclusions of the study shows that an appropriate product design and delivery, preventation of over-indebtedness, transparency, responsible pricing, fair and respectful treatment of clients, privacy of client data and mechanisms for complaint resolution is best way for the operational and financial sustainability of microfinance institutions. The findings of the study will benefited policy makers and leader of microfinance institutions. Accodingly, this paper explores the state of responsible financial knowledge and practices, with a focus on client protection and client’s satisfaction strategies on the basis of review of best practices.